Rate of premalignant and malignant endometrial lesion in "low-risk" premenopausal women with abnormal uterine bleeding undergoing endometrial biopsy - Sangam Jha; Akanksha Singh; Hemali Heidi Sinha; Poonam Bhadani; Monika Anant; Mukta Agarwal (Korean Society of Obstetrics and Gynecology, 2021)
Objective To determine the incidence of endometrial hyperplasia and endometrial cancer (EH/EC) in low-risk premenopausal women with abnormal uterine bleeding (AUB) undergoing endometrial biopsy and to build a predictive model that includes clinical variables for predicting EH/EC in these women. Methods This retrospective study was conducted between January 2015 and March 2020. All premenopausal women aged <55 years with AUB who underwent endometrial sampling during a specified time period were included. Data regarding baseline characteristics, sonographic findings, and histological reports were collected from patient record sheets. Results During the specified time period, 1,089 premenopausal women underwent endometrial biopsy for AUB. Complete data analysis was done for 1,084 women. Of the endometrial samples, 95.3% revealed benign pathology, whereas 4.7% of the samples had major endometrial pathology EH/EC. On step-wise logistic regression analysis, intermenstrual bleeding (IMB) (OR, 3.15), body mass index (BMI) >25 kg/m2 (odds ratio [OR], 4.4705), age >40 years (OR, 1.14), endometrial thickness (ET) >13 mm (OR, 2.59), and hypothyroidism (OR, 1.35) were significantly associated with EH/ EC. Considering the pretest probability for an EH/EC of 4.7%, this prediction model with a likelihood ratio of 14.2% demonstrated a post-test probability of 41% in the presence of the above-mentioned variables. Conclusion The risk of EH/EC was lower in low-risk premenopausal women with AUB. However, premenopausal women with IMB aged >40 years, hypothyroidism, BMI >25 kg/m2, and thickened endometrium (ET >13 mm) are at high risk of EH/EC; therefore, endometrial biopsy should be considered early in their management plan.